Morphology of the Homo naledi femora from Lesedi. Issue 1 (22nd June 2019) - Walker, Christopher S.; Cofran, Zachary D.; Grabowski, Mark; Marchi, Damiano; Cook, Rebecca W.; Churchill, Steven E.; Tommy, Kimberleigh A.; Throckmorton, Zachary; Ross, Ann H.; Hawks, John; Yapuncich, Gabriel S.; Van Arsdale, Adam P.; et al.
Abstract: Objectives: The femoral remains recovered from the Lesedi Chamber are among the most complete South African fossil hominin femora discovered to date and offer new and valuable insights into the anatomy and variation of the bone in Homo naledi . While the femur is one of the best represented postcranial elements in the H. naledi assemblage from the Dinaledi Chamber, the fragmentary and commingled nature of the Dinaledi femoral remains has impeded the assessment of this element in its complete state. Materials and methods: Here we analyze and provide descriptions of three new relatively well‐preserved femoral specimens of H. naledi from the Lesedi Chamber: U.W. 102a‐001, U.W. 102a‐003, and U.W. 102a‐004. These femora are quantitatively and qualitatively compared to multiple extinct hominin femoral specimens, extant hominid taxa, and, where possible, each other. Results: The Lesedi femora are morphologically similar to the Dinaledi femora for all overlapping regions, with differences limited to few traits of presently unknown significance. The Lesedi distal femur and mid‐diaphysis preserve anatomy previously unidentified or unconfirmed in the species, including an anteroposteriorly expanded midshaft and anteriorly expanded patellar surface. The hypothesis that the Lesedi femoral sample may represent two individuals is supported. Discussion: The Lesedi femora increase the range of variation of femoral morphology in H. naledi . Newly described features of the diaphysis and distal femur are either taxonomically uninformative or Homo ‐like. Overall, these three new femora are consistent with previous functional interpretations of the H. naledi lower limb as belonging to a species adapted for long distance walking and, possibly, running.